An antibacterial degradable packaging box coating based on chitosan-silver ions and a preparation method thereof
Patent Information
- Application Number
- CN202610856563.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-06-15
AI Technical Summary
[0004]但是,以上述技术路线为代表的现有技术主要存在以下的技术问题:单一可降解材料往往更侧重于成型和降解性能,表面功能较为有限,难以同时兼顾包装使用过程中的抗菌需求;部分表面涂层与基材之间结合稳定性不足,容易出现涂层分布不均、附着力不理想或使用过程中性能衰减的问题;部分抗菌体系虽然能够提供一定抑菌效果,但与可降解材料体系之间的相容性、加工适配性及安全性协调不足,容易影响包装盒整体的使用稳定性与应用范围;此外,现有方案中还普遍存在材料组成复杂、制备过程衔接性不强、绿色包装属性与抗菌功能之间难以协同统一的问题
本发明在可降解包装盒基材表面设置由单宁酸、钙盐和羧甲基纤维素钠形成的基材锚定层,使单宁酸的多酚结构、钙离子和纤维素类成膜组分共同参与界面结合。该层不是单纯作为底涂层使用,而是在基材表面形成可与后续海藻酸钠发生离子配位的过渡界面,从而使涂层与纸浆模塑、淀粉基或聚乳酸类基材之间具有更明确的衔接基础,减少单层壳聚糖涂层在可降解基材表面附着不均的问题。
Smart Images

Figure CN122405067B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of antibacterial and biodegradable packaging materials, specifically relating to an antibacterial and biodegradable packaging box coating based on chitosan-silver ions and its preparation method. Background Technology
[0002] With the continued growth in demand for food, fresh produce, e-commerce delivery, and disposable catering packaging, packaging materials are gradually evolving towards green and functional directions, in addition to meeting basic requirements for forming, load-bearing, and barrier properties. Biodegradable packaging boxes, due to their wide availability and low environmental impact after disposal, have become an important development direction for replacing some traditional plastic packaging. Building on this, to further adapt to the requirements of hygiene, safety, surface stability, and preservation conditions during food storage and transportation, endowing packaging box surfaces with certain antibacterial properties has become an important aspect of food packaging material research and development.
[0003] Among the relevant existing technologies, typical technical routes include: First, directly using pulp molding materials, starch-based materials, polylactic acid materials, or other bio-based materials to prepare biodegradable packaging boxes to improve the environmental friendliness of the materials; Second, compounding natural polymer film-forming substances on the surface of the packaging box to form a protective layer to improve surface density, water resistance, or barrier properties; Third, introducing organic antibacterial agents, plant extracts, metal ions, or inorganic antibacterial particles into the packaging material itself or surface coating to give the packaging material antibacterial capabilities.
[0004] However, existing technologies represented by the above-mentioned technical routes mainly have the following technical problems: single biodegradable materials often focus more on molding and degradation performance, with limited surface functions, making it difficult to simultaneously meet the antibacterial requirements during packaging use; the bonding stability between some surface coatings and the substrate is insufficient, easily leading to uneven coating distribution, poor adhesion, or performance degradation during use; although some antibacterial systems can provide a certain antibacterial effect, their compatibility, processing adaptability, and safety coordination with biodegradable material systems are insufficient, easily affecting the overall stability and application range of the packaging box; in addition, existing solutions generally suffer from complex material composition, weak connection between preparation processes, and difficulty in synergistically unifying green packaging attributes and antibacterial functions.
[0005] Therefore, it is necessary to propose a technical solution for surface modification of existing biodegradable packaging boxes, addressing their limited functionality, insufficient antibacterial properties, and inadequate synergy with material systems, in order to promote the further application of biodegradable packaging materials in the food packaging field. Summary of the Invention
[0006] To address the aforementioned problems, the present invention aims to provide an antibacterial and biodegradable packaging box coating based on chitosan-silver ions. The antibacterial and biodegradable packaging box coating is formed on at least one surface of a biodegradable packaging box substrate. By dry weight, the antibacterial and biodegradable packaging box coating comprises: a substrate anchoring layer, a chitosan-silver ion confinement layer, and a biodegradable sealing layer.
[0007] As a preferred technical solution, the substrate anchoring layer comprises 2-12 parts tannic acid, 0.5-5 parts calcium salt, and 1-8 parts sodium carboxymethyl cellulose; the chitosan-silver ion confinement layer comprises 100 parts water-soluble chitosan, 0.3-6 parts silver salt, 15-70 parts sodium alginate, 3-18 parts low molecular weight citric acid, and 2-15 parts glycerol; the biodegradable sealing layer comprises 20-80 parts wax microemulsion component, 10-45 parts low ester pectin, 5-35 parts polyvinyl alcohol, and 2-12 parts citric acid.
[0008] As a preferred technical solution, the substrate anchoring layer is located between the biodegradable packaging box substrate and the chitosan-silver ion confinement layer; the biodegradable sealing layer covers the outside of the chitosan-silver ion confinement layer.
[0009] As a preferred technical solution, the water-soluble chitosan in the chitosan-silver ion confinement layer forms a chitosan-silver ion complex with silver salt; the sodium alginate forms a calcium alginate confinement structure with calcium ions from the substrate anchoring layer; the total dry film thickness of the antibacterial and biodegradable packaging box coating is 5-28 μm, and the silver element accounts for 0.05%-0.9% of the total dry weight of the antibacterial and biodegradable packaging box coating.
[0010] As a preferred technical solution, the biodegradable packaging box substrate is one of sugarcane bagasse pulp molding substrate, bamboo pulp molding substrate, wheat straw pulp molding substrate, starch-based molding substrate, or polylactic acid sheet.
[0011] As a preferred technical solution, the surface of the biodegradable packaging box substrate to be coated is formed by plasma treatment or corona treatment to form an oxygen-containing active surface. The dyne value of the treated surface to be coated is 38-56 mN / m, and the surface moisture content is 5%-11%.
[0012] As a preferred technical solution, in the substrate anchoring layer: the weight ratio of tannic acid to calcium salt is 2:1 to 10:1; the calcium salt is one or two of calcium chloride, calcium lactate, or calcium gluconate; the degree of substitution of sodium carboxymethyl cellulose is 0.6 to 1.2; the dry film thickness of the substrate anchoring layer is 0.3 to 3 μm; the substrate anchoring layer is a continuous anchoring film layer containing tannic acid, calcium salt, and sodium carboxymethyl cellulose, and the continuous anchoring film layer covers the surface of the biodegradable packaging box substrate to be coated.
[0013] As a preferred technical solution, in the chitosan-silver ion confinement layer: the water-soluble chitosan is carboxymethyl chitosan or quaternized chitosan; the degree of deacetylation of the water-soluble chitosan is 75% to 95%, and the viscosity-average molecular weight is 50,000 to 300,000; the silver salt is one of silver lactate, silver citrate, or silver nitrate.
[0014] As a preferred technical solution, the silver salt is first mixed with water-soluble chitosan to form a chitosan-silver ion complex, and then mixed with sodium alginate to form a film-forming component for the chitosan-silver ion confinement layer, wherein the weight ratio of sodium alginate to water-soluble chitosan is 0.15:1 to 0.7:1.
[0015] As a preferred technical solution, the dry film thickness of the chitosan-silver ion confinement layer is 3-18 μm; the chitosan-silver ion confinement layer contains a silver-containing dispersed phase with a particle size of 5-80 nm, and the number of silver-containing agglomerates with a maximum outer diameter greater than 250 nm in any 100 μm × 100 μm observation area is no more than 6; the silver-containing dispersed phase is located within the interwoven film phase formed by water-soluble chitosan and sodium alginate.
[0016] As a preferred technical solution, the waxy microemulsion component in the biodegradable sealing layer is made of at least one of carnauba wax, rice bran wax, or beeswax; the dispersed phase particle size D50 of the waxy microemulsion component is 0.2–3 μm; the degree of esterification of the low-ester pectin is 20%–45%; the dry film thickness of the biodegradable sealing layer is 1–7 μm; and the weight ratio of the waxy microemulsion component to the low-ester pectin is 1:0.2–1:1.5.
[0017] As a preferred technical solution, the substrate anchoring layer, the chitosan-silver ion confinement layer, and the biodegradable sealing layer form a continuous stacked structure; the chitosan-silver ion confinement layer has a calcium alginate confinement interface on the side near the substrate anchoring layer, and the thickness of the calcium alginate confinement interface is 0.1-2 μm; the calcium alginate confinement interface contains a calcium alginate component formed by sodium alginate and calcium ions; the chitosan-silver ion confinement layer has a citric acid crosslinking interface on the side near the biodegradable sealing layer, and the thickness of the citric acid crosslinking interface is 0.1-2 μm, and the citric acid crosslinking interface contains water-soluble chitosan, low-ester pectin, polyvinyl alcohol, and citric acid.
[0018] The present invention also provides a method for preparing the chitosan-silver ion-based antibacterial and biodegradable packaging box coating, comprising the following steps: S1. Substrate surface finishing: The surface of the biodegradable packaging box substrate to be coated is dusted, free fibers are removed, and plasma or corona treatment is performed to obtain a pretreated substrate with a surface moisture content of 5% to 11%. S2, Anchoring layer formation: An aqueous anchoring solution containing tannic acid, calcium salt and sodium carboxymethyl cellulose is applied to the surface of the pretreated substrate to be coated, and dried at 35-70°C to form the substrate anchoring layer; S3, Silver ion pre-complexation: Dissolve water-soluble chitosan in an aqueous medium, adjust the pH to 4.2-6.2, add silver salt and stir for 20-120 min to obtain chitosan-silver ion complex solution; S4. Preparation of confined coating solution: Add sodium alginate, low molecular weight citric acid and glycerol to chitosan-silver ion complex solution and stir until the viscosity is 80-900 mPa·s to obtain confined coating solution. S5. Formation of confinement layer: The confinement coating liquid is applied to the surface of the substrate anchoring layer and dried in sections at 40-85°C to form a chitosan-silver ion confinement layer. S6. Formation of the sealing layer: An aqueous sealing liquid containing waxy microemulsion components, low-ester pectin, polyvinyl alcohol and citric acid is coated on the surface of the chitosan-silver ion confinement layer and dried at 35-75°C to form a biodegradable sealing layer, thereby obtaining a packaging box with the aforementioned antibacterial and biodegradable packaging box coating.
[0019] As a preferred technical solution, in step S3, the mass concentration of water-soluble chitosan in the aqueous medium is 0.8% to 6%, and silver salt is added dropwise to the water-soluble chitosan solution in the form of a 0.01 to 0.3 mol / L silver salt aqueous solution for 15 to 80 min. The stirring speed during the dropwise addition process is 300 to 1000 r / min. After the dropwise addition is completed, the mixture is stirred in the dark for 20 to 120 min. In step S4, sodium alginate is added in the form of a sodium alginate aqueous solution with a mass concentration of 0.5% to 5%.
[0020] As a preferred technical solution, the segmented drying in step S5 includes a first drying stage and a second drying stage: the temperature of the first drying stage is 40-55℃ and the time is 3-15 min; the temperature of the second drying stage is 60-85℃ and the time is 5-30 min.
[0021] As a preferred technical solution, the preparation of the aqueous sealing liquid in step S6 includes melting the wax component at 60-90°C and then mixing and emulsifying it with a low-ester pectin aqueous solution, a polyvinyl alcohol aqueous solution, and citric acid. The dispersed phase particle size D50 of the wax microemulsion component in the emulsified aqueous sealing liquid is 0.2-3 μm.
[0022] As a preferred technical solution, the drying temperature in step S6 is lower than the temperature in the second drying stage.
[0023] Beneficial effects This invention provides a substrate anchoring layer on the surface of a biodegradable packaging substrate, composed of tannic acid, calcium salts, and sodium carboxymethyl cellulose. This allows the polyphenolic structure of tannic acid, calcium ions, and cellulose-based film-forming components to participate in interfacial bonding. This layer is not simply used as a base coat; rather, it forms a transitional interface on the substrate surface that can ionize with subsequent sodium alginate application. This provides a clearer bonding foundation between the coating and pulp molding, starch-based, or polylactic acid-based substrates, reducing the problem of uneven adhesion of single-layer chitosan coatings on the biodegradable substrate surface.
[0024] This invention first forms a chitosan-silver ion complex by combining water-soluble chitosan with silver salts, then introduces sodium alginate, low molecular weight citric acid, and glycerol to form a chitosan-silver ion confinement layer, and uses calcium ions from the substrate anchoring layer to form a calcium alginate confinement interface. This structure places the silver-containing dispersed phase within the interwoven film phase composed of chitosan and sodium alginate, avoiding localized aggregation or uneven migration caused by direct dispersion of silver salts in the coating, resulting in a more stable distribution of the antibacterial components within the biodegradable coating.
[0025] This invention provides a biodegradable sealing layer composed of a waxy microemulsion component, low-ester pectin, polyvinyl alcohol, and citric acid, located outside the chitosan-silver ion confinement layer, with citric acid cross-linking interfaces formed at adjacent interfaces. This sealing layer is not a simple hydrophobic capping layer, but rather a continuous outer layer formed by the waxy microemulsion and hydrophilic polymers. This prevents the silver ion confinement layer from being directly exposed to the packaging environment while retaining the biodegradable material properties of the coating. This creates a continuous and synergistic surface modification structure encompassing anchoring, confinement, and sealing layers. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the preparation method of the present invention; Figure 2 This is a schematic diagram of the area rate of detachment from the grid in the comparative experiment of this invention; Figure 3 This is a schematic diagram of the total dry film thickness in the comparative experiment of this invention; Figure 4 This is a schematic diagram showing the number of silver-containing aggregates in the comparative experiment of this invention; Figure 5 This is a schematic diagram of the antibacterial rate in the comparative experiment of this invention; Figure 6 This is a schematic diagram of water vapor transmission rate in the comparative experiment of this invention; Figure 7 This is a schematic diagram of the wet wiping mass change rate in the comparative experiment of this invention; Figure 8 This is a schematic diagram of the amount of silver migration in the comparative experiment of this invention. Detailed Implementation
[0027] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0028] Experimental group T1: T1 uses the low-parameter scheme of this invention to prepare an antibacterial and biodegradable packaging box coating based on chitosan-silver ions. Bamboo pulp molded packaging boxes are selected as the biodegradable packaging box substrate. The inner surface of the packaging box is subjected to dust removal treatment to remove free fibers and dust, followed by plasma treatment to control the moisture content of the surface to be coated to 5%–7% and the dyne value to 38–42 mN / m, thus obtaining the pretreated substrate.
[0029] The substrate anchoring layer is prepared by using an aqueous anchoring solution made of 2 parts tannic acid, 0.5 parts calcium chloride, and 1 part sodium carboxymethyl cellulose on a dry basis. The degree of substitution of sodium carboxymethyl cellulose is 0.6. The aqueous anchoring solution is uniformly applied to the surface of the pretreated substrate to be coated and dried at 35°C to form a substrate anchoring layer with a dry film thickness of approximately 0.3 μm.
[0030] The chitosan-silver ion confinement layer consists of 100 parts carboxymethyl chitosan, 0.3 parts silver citrate, 15 parts sodium alginate, 3 parts low molecular weight citric acid, and 2 parts glycerol. The degree of deacetylation of the carboxymethyl chitosan is 75%, and its viscosity-average molecular weight is 50,000. The preparation method is as follows: Figure 1 As shown, carboxymethyl chitosan was first dissolved in an aqueous medium, the pH was adjusted to 4.2, silver citrate was added and stirred for 20 min to form a chitosan-silver ion complex solution; then sodium alginate, low molecular weight citric acid and glycerol were added and stirred to obtain a confined coating solution. The confined coating solution was coated on the surface of the substrate anchoring layer, and after a first drying stage at 40℃ and a second drying stage at 60℃, a chitosan-silver ion confined layer with a dry film thickness of about 3 μm was formed.
[0031] The biodegradable sealing layer consists of 20 parts of a waxy microemulsion, 10 parts of low-ester pectin, 5 parts of polyvinyl alcohol, and 2 parts of citric acid. The waxy microemulsion is made from rice bran wax, and the low-ester pectin has an esterification degree of 20%. An aqueous sealing solution containing the waxy microemulsion, low-ester pectin, polyvinyl alcohol, and citric acid is coated onto the surface of the chitosan-silver ion confinement layer and dried at 35°C to form a biodegradable sealing layer with a dry film thickness of approximately 1 μm, yielding the T1 packaging box sample.
[0032] Experimental group T2: T2 uses the parameter scheme of this invention to prepare an antibacterial and biodegradable packaging box coating based on chitosan-silver ions. Bamboo pulp molded packaging boxes are selected as the biodegradable packaging box substrate. The inner surface of the packaging box is subjected to dust removal treatment to remove free fibers and dust, followed by plasma treatment to control the moisture content of the surface to be coated to 7%–9% and the dyne value to 45–50 mN / m, thus obtaining the pretreated substrate.
[0033] Based on dry weight, the substrate anchoring layer is prepared with an aqueous anchoring solution consisting of 7 parts tannic acid, 2.5 parts calcium chloride, and 4.5 parts sodium carboxymethyl cellulose, wherein the degree of substitution of sodium carboxymethyl cellulose is 0.9. The aqueous anchoring solution is uniformly coated onto the surface of the pretreated substrate to be coated and dried at 55°C to form a substrate anchoring layer with a dry film thickness of approximately 1.6 μm.
[0034] The chitosan-silver ion confinement layer consists of 100 parts carboxymethyl chitosan, 3 parts silver citrate, 42 parts sodium alginate, 10 parts low molecular weight citric acid, and 8 parts glycerol. The degree of deacetylation of carboxymethyl chitosan is 85%, and its viscosity-average molecular weight is 180,000. First, carboxymethyl chitosan is dissolved in an aqueous medium, the pH is adjusted to 5.2, silver citrate is added, and the mixture is stirred for 70 min to form a chitosan-silver ion complex solution. Then, sodium alginate, low molecular weight citric acid, and glycerol are added, and the mixture is stirred until the viscosity reaches approximately 450 mPa·s to obtain the confinement coating solution. The confinement coating solution is coated onto the surface of the substrate anchoring layer. After a first drying stage at 50℃ and a second drying stage at 72℃, a chitosan-silver ion confinement layer with a dry film thickness of approximately 10 μm is formed.
[0035] The biodegradable sealing layer consists of 50 parts of a waxy microemulsion, 28 parts of low-ester pectin, 20 parts of polyvinyl alcohol, and 7 parts of citric acid. The waxy microemulsion is made from rice bran wax, and the low-ester pectin has an esterification degree of 32%. An aqueous sealing solution containing the waxy microemulsion, low-ester pectin, polyvinyl alcohol, and citric acid is coated onto the surface of the chitosan-silver ion confinement layer and dried at 55°C to form a biodegradable sealing layer with a dry film thickness of approximately 4 μm, yielding the T2 packaging box sample.
[0036] Experimental group T3: T3 employs the high-parameter scheme of this invention to prepare an antibacterial and biodegradable packaging box coating based on chitosan-silver ions. Bamboo pulp molded packaging boxes are selected as the biodegradable packaging box substrate. The inner surface of the packaging box undergoes dust removal treatment to remove free fibers and dust, followed by plasma treatment to control the moisture content of the surface to be coated to 9%–11% and the dyne value to 52–56 mN / m, resulting in a pretreated substrate.
[0037] The substrate anchoring layer is prepared by using an aqueous anchoring solution of 12 parts tannic acid, 5 parts calcium chloride, and 8 parts sodium carboxymethyl cellulose on a dry basis, wherein the degree of substitution of sodium carboxymethyl cellulose is 1.2. The aqueous anchoring solution is uniformly coated onto the surface of the pretreated substrate to be coated and dried at 70°C to form a substrate anchoring layer with a dry film thickness of approximately 3 μm.
[0038] The chitosan-silver ion confinement layer consists of 100 parts carboxymethyl chitosan, 6 parts silver citrate, 70 parts sodium alginate, 18 parts low molecular weight citric acid, and 15 parts glycerol. The degree of deacetylation of the carboxymethyl chitosan is 95%, and its viscosity-average molecular weight is 300,000. First, the carboxymethyl chitosan is dissolved in an aqueous medium, the pH is adjusted to 6.2, silver citrate is added, and the mixture is stirred for 120 min to form a chitosan-silver ion complex solution. Then, sodium alginate, low molecular weight citric acid, and glycerol are added, and the mixture is stirred until the viscosity is approximately 900 mPa·s to obtain the confinement coating solution. The confinement coating solution is coated onto the surface of the substrate anchoring layer. After a first drying stage at 55℃ and a second drying stage at 85℃, a chitosan-silver ion confinement layer with a dry film thickness of approximately 18 μm is formed.
[0039] The biodegradable sealing layer consists of 80 parts of a waxy microemulsion, 45 parts of low-ester pectin, 35 parts of polyvinyl alcohol, and 12 parts of citric acid. The waxy microemulsion is made from rice bran wax, and the low-ester pectin has an esterification degree of 45%. An aqueous sealing solution containing the waxy microemulsion, low-ester pectin, polyvinyl alcohol, and citric acid is coated onto the surface of the chitosan-silver ion confinement layer and dried at 75°C to form a biodegradable sealing layer with a dry film thickness of approximately 7 μm, yielding the T3 packaging box sample.
[0040] Comparative Example C1: C1 was used to investigate the impact on the coating structure when no substrate anchoring layer was provided. The same bamboo pulp molded packaging box as T2 was selected as the biodegradable packaging box substrate, and the same dust removal, free fiber removal and plasma treatment conditions as T2 were used to obtain the pretreated substrate.
[0041] Unlike T2, C1 does not use an aqueous anchoring solution containing tannic acid, calcium chloride, and sodium carboxymethyl cellulose, thus not forming a substrate anchoring layer. Subsequently, a confinement coating solution is directly applied to the pretreated substrate surface to be coated. The composition and preparation method of the confinement coating solution are the same as T2, using 100 parts carboxymethyl chitosan, 3 parts silver citrate, 42 parts sodium alginate, 10 parts low molecular weight citric acid, and 8 parts glycerol. First, a chitosan-silver ion complex solution is prepared, then sodium alginate, low molecular weight citric acid, and glycerol are added. After applying the confinement coating solution, a chitosan-silver ion confinement layer is formed under the same segmented drying conditions as T2. Then, a biodegradable sealing layer is formed under the same sealing layer composition and drying conditions as T2, resulting in the C1 packaging box sample.
[0042] Comparative Example C2: C2 was used to investigate the effect of not performing chitosan-silver ion pre-complexation on the distribution of silver-containing components. The same bamboo pulp molded packaging box as T2 was selected as the biodegradable packaging box substrate, and the substrate anchoring layer was formed under the same conditions as T2.
[0043] Unlike T2, C2 does not first form a chitosan-silver ion complex with carboxymethyl chitosan and silver citrate when preparing the chitosan-silver ion confinement layer. Instead, 100 parts of carboxymethyl chitosan, 3 parts of silver citrate, 42 parts of sodium alginate, 10 parts of low molecular weight citric acid, and 8 parts of glycerol are simultaneously added to an aqueous medium and stirred to form a common silver-containing coating solution. This common silver-containing coating solution is then applied to the surface of the substrate anchoring layer, and a silver-containing film layer is formed under the same segmented drying conditions as T2. Subsequently, a biodegradable sealing layer is formed under the same sealing layer composition and drying conditions as T2, resulting in the C2 packaging box sample.
[0044] Comparative Example C3: C3 was used to investigate the effect of not introducing sodium alginate on the calcium alginate confined structure. The same bamboo pulp molded packaging box as T2 was selected as the biodegradable packaging box substrate, and the substrate anchoring layer was formed under the same conditions as T2.
[0045] Unlike T2, C3's chitosan-silver ion confinement layer does not contain sodium alginate. The remaining components consist of 100 parts carboxymethyl chitosan, 3 parts silver citrate, 10 parts low molecular weight citric acid, and 8 parts glycerol. In preparation, carboxymethyl chitosan is first dissolved in an aqueous medium, the pH is adjusted to 5.2, silver citrate is added, and the mixture is stirred for 70 minutes to form a chitosan-silver ion complex. Then, low molecular weight citric acid and glycerol are added to obtain a coating solution without sodium alginate. This coating solution is applied to the surface of the substrate anchoring layer, and a chitosan-silver ion film layer without sodium alginate is formed under the same segmented drying conditions as T2. Subsequently, a biodegradable sealing layer is formed under the same sealing layer composition and drying conditions as T2, resulting in the C3 packaging box sample.
[0046] Comparative Example C4: C4 was used to investigate the impact on the outer structure of the coating without a biodegradable sealing layer. The same bamboo pulp molded packaging box as T2 was selected as the biodegradable packaging box substrate, and the substrate anchoring layer and chitosan-silver ion confinement layer were formed under the same conditions as T2.
[0047] Unlike T2, C4 does not form a biodegradable sealing layer after the chitosan-silver ion confinement layer is formed. Instead, it is coated with an aqueous sealing solution containing waxy microemulsion components, low-ester pectin, polyvinyl alcohol, and citric acid. All other substrate treatment conditions, anchoring layer composition, silver ion pre-complexation conditions, confinement coating solution composition, coating conditions, and segmented drying conditions remain consistent with T2, resulting in the C4 packaging box sample.
[0048] Comparative Example C5: C5 was used to investigate the impact of replacing the composite biodegradable sealing layer with a single wax sealing layer. The same bamboo pulp molded packaging box as T2 was selected as the biodegradable packaging box substrate, and the substrate anchoring layer and chitosan-silver ion confinement layer were formed under the same conditions as T2.
[0049] Unlike T2, C5's outer layer does not use an aqueous sealing solution containing waxy microemulsion components, low-ester pectin, polyvinyl alcohol, and citric acid. Instead, it uses only 50 parts of a waxy microemulsion component made from rice bran wax to prepare a single waxy sealing solution. This single waxy sealing solution is coated onto the surface of the chitosan-silver ion confinement layer and dried at 55°C to form a single waxy sealing layer. All other substrate treatment conditions, anchoring layer composition, silver ion pre-complexation conditions, confinement coating solution composition, coating conditions, and segmented drying conditions remain consistent with T2, resulting in the C5 packaging box sample.
[0050] Comparative Example C6: C6 was used to investigate the effect of not introducing low-ester pectin on the structure of the composite biodegradable sealing layer. The same bamboo pulp molded packaging box as T2 was selected as the biodegradable packaging box substrate, and the substrate anchoring layer and chitosan-silver ion confinement layer were formed under the same conditions as T2.
[0051] Unlike T2, C6's biodegradable sealing layer does not contain low-ester pectin. The remaining sealing layer components consist of 50 parts waxy microemulsion, 20 parts polyvinyl alcohol, and 7 parts citric acid. An aqueous sealing solution containing the waxy microemulsion, polyvinyl alcohol, and citric acid is coated onto the surface of the chitosan-silver ion confinement layer and dried at 55°C to form a biodegradable sealing layer without low-ester pectin. All other substrate treatment conditions, anchoring layer composition, silver ion pre-complexation conditions, confinement coating solution composition, coating conditions, and segmented drying conditions remain consistent with T2, resulting in the C6 packaging box sample.
[0052] The following comparative experimental parameters and testing methods are used to evaluate the structural stability, antibacterial effect, barrier properties, and biodegradability of T1-T3 and C1-C6 coatings: 1. Coating adhesion Test objective: To evaluate the influence of the substrate anchoring layer on the bonding stability between the coating and the bamboo pulp molded packaging box substrate.
[0053] Testing method: The cross-cut adhesion test is used. Evenly spaced grids are drawn on the coating surface of the packaging box. Standard tape is applied and peeled off at a fixed angle. After peeling, the area of coating peeling off within the grid area is observed and counted. The cross-cut adhesion peeling area rate is calculated using the following formula: The area of coating peeling off the grid is calculated as follows: (Area of coating peeling off ÷ Total area of the gridded area) × 100%.
[0054] Each sample group should be tested at no fewer than 5 locations, and the average value should be taken. The lower the cross-cutting peeling area rate, the more stable the bond between the coating and the bamboo pulp molded packaging box substrate.
[0055] 2. Coating thickness and uniformity Test objective: To evaluate the overall coating consistency after the formation of the substrate anchoring layer, chitosan-silver ion confinement layer, and biodegradable sealing layer.
[0056] Testing method: Cut a sample of the coating from the packaging box, observe the cross-section of the coating using a cross-sectional microscope or scanning electron microscope, and measure the total dry film thickness; select no less than 10 measurement points for each sample, and calculate the average thickness and thickness deviation. If necessary, energy dispersive spectroscopy (EDS) analysis can be used to observe the distribution of silver-containing components within the coating.
[0057] 3. Dispersion state of silver-containing components Objective: To evaluate the effects of chitosan-silver ion pre-complexation and sodium alginate confinement treatment on the dispersion state of silver-containing components.
[0058] Detection method: Take a cross-section or surface sample of the coating and use scanning electron microscopy combined with energy dispersive spectroscopy to observe the distribution of the silver-containing dispersed phase; record the number of silver-containing aggregates with a maximum outer diameter greater than 250 nm in any 100 μm × 100 μm observation area. Select no less than 5 observation areas for each group of samples and take the average value.
[0059] 4. Antibacterial properties Objective: To evaluate the effect of the chitosan-silver ion confinement layer on the antibacterial properties of the packaging box surface.
[0060] Detection method: Escherichia coli and Staphylococcus aureus were selected as test bacteria. The bacterial solution was brought into contact with the coating surface and incubated for a certain period of time under specified temperature and humidity conditions. Afterwards, the bacteria were washed off and the number of viable bacteria was counted to calculate the inhibition rate. At least three parallel samples were set up for each group of samples, and the inhibition results of the two bacterial species were recorded separately.
[0061] 5. Water vapor transmission rate Objective: To evaluate the impact of biodegradable sealing layers on the moisture barrier properties of packaging box coatings.
[0062] Test method: Cut the coating samples to a uniform size and test them using a water vapor transmission rate tester or a gravimetric method. Measure the water vapor transmission rate per unit area and per unit time under fixed temperature and relative humidity conditions. Test at least three parallel samples for each group and take the average value.
[0063] 6. Surface resistance to wet wiping Test objective: To evaluate the surface integrity and outer layer sealing stability of the coating under wet contact conditions.
[0064] Test method: Wet the non-woven fabric with deionized water, and wipe the coating surface of the packaging box under the same pressure and the same number of reciprocating strokes. Observe the coating peeling, whitening, powdering, or exposure of the substrate, and record the sample mass change rate before and after wiping. Each group of samples should have no less than 3 parallel samples tested.
[0065] 7. Silver migration Objective: To evaluate the effects of the biodegradable sealing layer and the chitosan-silver ion confinement layer on the migration behavior of the silver component.
[0066] Testing method: Following the migration testing approach for food contact materials, the coated sample was contacted with a simulated food solution (3% acetic acid aqueous solution) and extracted at a set temperature and time. The silver content of the extract was determined by inductively coupled plasma atomic emission spectrometry or atomic absorption spectrometry, and the silver migration per unit area was calculated. At least three parallel samples were tested for each group of samples.
[0067] The experimental data are shown in Tables 1 and 2: Table 1 Comparative Experimental Data (I)
[0068] Table 2 Comparative Experimental Data (II)
[0069] Data Analysis: The data in the table shows that T1-T3 all formed relatively complete laminated structures consisting of a substrate anchoring layer, a chitosan-silver ion confinement layer, and a biodegradable sealing layer. Among them, T2 exhibits more balanced overall performance, such as... Figure 2 As shown, the area rate of detachment from the grid was 2.1±0.4%, which was significantly lower than that of C1 (18.6±2.1%). This indicates that the substrate anchoring layer formed by tannic acid, calcium chloride, and sodium carboxymethyl cellulose was not a common base coating, but rather formed a continuous transition bonding interface on the surface of the bamboo pulp molded packaging box substrate.
[0070] The polyphenol structure in tannic acid can form multiple binding sites with the surface of cellulose substrate, sodium carboxymethyl cellulose can improve the spreading continuity of aqueous anchoring liquid on the fiber surface, and the calcium ions provided by calcium chloride can further participate in the subsequent ion binding of sodium alginate.
[0071] Therefore, without a substrate anchoring layer, the coating of C1 is directly attached to the surface of the bamboo pulp molded substrate. Although it still contains chitosan, silver salt, sodium alginate and a sealing layer, it lacks bottom anchoring and calcium ion transition interface, resulting in a significant increase in both the coating peeling area rate and the wet scrubbing quality change rate.
[0072] Regarding the dispersion state of the silver-containing components, the number of silver-containing aggregates in T2 was 2.1 ± 0.5 per 100 μm × 100 μm, while C2 increased to 12.6 ± 1.4 per 100 μm × 100 μm, and C3 increased to 8.7 ± 1.1 per 100 μm × 100 μm. These results indicate that the treatment method employed in this invention, which involves "first forming a chitosan-silver ion complex with carboxymethyl chitosan and silver citrate, then adding sodium alginate, low molecular weight citric acid, and glycerol," enables the silver component to be first dispersed and complexed by adjacent amino, hydroxyl, or carboxyl groups in the chitosan chain segments, and then enters the interwoven membrane phase formed with the participation of sodium alginate. C2 mixes all components simultaneously, but the silver salt lacks a pre-complexation and dispersion process, making it prone to forming silver-containing aggregates in localized areas. C3, without the addition of sodium alginate, can still form chitosan-silver ion complexes, but lacks the confined structure formed by sodium alginate and calcium ions, making the silver-containing components more likely to migrate and concentrate during the drying and film-forming process. Therefore, T2 exhibits better coordination between the number of silver-containing aggregates, antibacterial properties, and silver migration.
[0073] From the perspective of antibacterial results, such as Figure 5 As shown, the inhibition rates of T2 against Escherichia coli and Staphylococcus aureus were 97.8±0.9% and 96.5±1.1%, respectively, which were higher than those of C2 (88.3±2.2% and 86.7±2.4%), and also higher than those of C3 (90.5±2.0% and 88.9±2.2%). This indicates that the present invention does not simply rely on increasing the amount of silver salt added to obtain the antibacterial effect, but rather achieves a relatively uniform dispersion of the silver-containing components in the coating through chitosan-silver ion complexation and sodium alginate confinement. Figure 4 As shown. The more uniformly the silver-containing components are dispersed, the more continuous the effective antibacterial contact area on the coating surface, and the fewer the antibacterial blank areas caused by local silver salt agglomeration. The antibacterial rate of T3 is slightly higher than that of T2, mainly due to its higher silver salt content, chitosan-silver ion confinement layer thickness, and total dry film thickness. Figure 3 As shown; however, the silver migration and 28-day mass loss rate of T3 were not better than those of T2, indicating that although excessively high parameters can increase the antibacterial component reserves and barrier thickness, they will create a certain trade-off in terms of biodegradability compatibility and material usage.
[0074] From the perspective of water vapor transmission rate and wet wiping quality change rate, T1-T3 increase with increasing coating thickness and amount of sealing layer component, such as Figure 6 As shown, the water vapor transmission rate is 286±12 g·m -2 24h -1 Reduced to 196±9 g·m -2 24h -1 This indicates that the biodegradable sealing layer formed by the wax microemulsion components, low-ester pectin, polyvinyl alcohol, and citric acid can improve the continuity of the outer side of the coating and reduce the rate at which water vapor passes through the coating.
[0075] C4 lacks a biodegradable sealing layer, resulting in a water vapor permeability that increases to 374±16 g·m. -2 24h -1 The wet wiping quality change rate increased to 6.2±0.6%, such as... Figure 7 As shown, the silver migration increased to 31.5 ± 2.6 μg·dm³. -2 ,like Figure 8 As shown, when the chitosan-silver ion confinement layer is directly exposed, the outer side of the coating lacks sufficient resistance to wet abrasion and barrier properties, making it easier for silver-containing components to migrate in the food simulation liquid. Therefore, the biodegradable sealing layer does not simply increase thickness, but rather serves to seal the outer layer, provide wet protection, and regulate migration.
[0076] After C5 replaced the composite biodegradable sealing layer with a single waxy sealing layer, the water vapor transmission rate was 241±12 g·m. -2 24h -1 The silver migration was 19.8 ± 1.7 μg·dm³. -2 Both were significantly higher than T2; after C6 was not introduced with low-ester pectin, the water vapor transmission rate and silver migration also increased to 259±13 g·m. -2 24h -1 and 17.2±1.4μg·dm -2 ,like Figure 6 , Figure 8 As shown in the figure. These results indicate that relying solely on the wax component to form a hydrophobic layer is insufficient to maintain the continuous bonding between the coating and the chitosan-silver ion confinement layer. Low-ester pectin and polyvinyl alcohol improve the film-forming continuity of the sealing layer, while citric acid participates in forming cross-linked structures at adjacent interfaces, ensuring that the relationship between the sealing layer and the confinement layer is not a simple covering, but rather a certain interfacial connection. When low-ester pectin is absent, the hydrophilic polymer network of the sealing layer is incomplete, reducing the continuous filling and interfacial stability between the wax microemulsion dispersed phases, thus decreasing both water vapor barrier and silver migration control effects.
[0077] In summary, the experimental data corresponds to the three core improvements of this invention: First, the tannic acid-calcium salt-carboxymethyl cellulose sodium substrate anchoring layer reduces the coating peeling area rate and improves the interfacial bonding between the coating and the bamboo pulp molding substrate. Second, the chitosan-silver ion pre-complexation and sodium alginate-calcium ion confinement structure reduce the number of silver-containing aggregates and reduce silver migration while maintaining antibacterial properties. Third, the biodegradable sealing layer composed of waxy microemulsion components, low-ester pectin, polyvinyl alcohol, and citric acid improves moisture barrier, wet rubbing stability, and outer sealing state.
[0078] The three technical means are applied to the substrate interface, the silver-containing confinement layer and the outer sealing layer respectively, and together form a continuous stacked structure, so that the present invention exhibits more complete and balanced comprehensive performance compared with each comparative example.
[0079] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antibacterial and biodegradable packaging box coating based on chitosan-silver ions, characterized in that, The antibacterial and biodegradable packaging box coating is formed on at least one surface of the biodegradable packaging box substrate, and on a dry basis by weight, the antibacterial and biodegradable packaging box coating comprises: a substrate anchoring layer, a chitosan-silver ion confinement layer, and a biodegradable sealing layer; The substrate anchoring layer comprises 2-12 parts tannic acid, 0.5-5 parts calcium salt, and 1-8 parts sodium carboxymethyl cellulose; The chitosan-silver ion confinement layer comprises 100 parts of water-soluble chitosan, 0.3-6 parts of silver salt, 15-70 parts of sodium alginate, 3-18 parts of citric acid, and 2-15 parts of glycerol; The biodegradable sealing layer comprises 20-80 parts of waxy microemulsion, 10-45 parts of low-ester pectin, 5-35 parts of polyvinyl alcohol, and 2-12 parts of citric acid; The substrate anchoring layer is located between the biodegradable packaging box substrate and the chitosan-silver ion confinement layer; The biodegradable sealing layer covers the outside of the chitosan-silver ion confinement layer; The water-soluble chitosan in the chitosan-silver ion confinement layer forms a chitosan-silver ion complex with the silver salt. The total dry film thickness of the antibacterial and biodegradable packaging box coating is 5–28 μm, and the silver element accounts for 0.05%–0.9% of the total dry weight of the antibacterial and biodegradable packaging box coating.
2. The antibacterial and biodegradable packaging box coating based on chitosan-silver ions according to claim 1, characterized in that, The biodegradable packaging box substrate is one of the following: sugarcane bagasse pulp molding substrate, bamboo pulp molding substrate, wheat straw pulp molding substrate, starch-based molding substrate, or polylactic acid sheet. The surface of the biodegradable packaging box substrate to be coated is formed by plasma treatment or corona treatment to form an oxygen-containing active surface. The dyne value of the treated surface to be coated is 38-56 mN / m, and the surface moisture content is 5%-11%.
3. The antibacterial and biodegradable packaging box coating based on chitosan-silver ions according to claim 1, characterized in that, In the substrate anchoring layer: The weight ratio of tannic acid to calcium salt is 2:1 to 10:1; The calcium salt is one or two of calcium chloride, calcium lactate, or calcium gluconate. The degree of substitution of the sodium carboxymethyl cellulose is 0.6 to 1.2; The dry film thickness of the substrate anchoring layer is 0.3–3 μm; The substrate anchoring layer is a continuous anchoring film layer containing tannic acid, calcium salt and sodium carboxymethyl cellulose, and the continuous anchoring film layer covers the surface of the biodegradable packaging box substrate to be coated.
4. The antibacterial and biodegradable packaging box coating based on chitosan-silver ions according to claim 1, characterized in that, In the chitosan-silver ion confinement layer: Water-soluble chitosan is carboxymethyl chitosan or quaternized chitosan; The degree of deacetylation of the water-soluble chitosan is 75%–95%, and the viscosity-average molecular weight is 50,000–300,000. The silver salt is one of silver lactate, silver citrate, or silver nitrate. The silver salt is first mixed with water-soluble chitosan to form a chitosan-silver ion complex, and then mixed with sodium alginate to form a film-forming component for the chitosan-silver ion confinement layer, wherein the weight ratio of sodium alginate to water-soluble chitosan is 0.15:1 to 0.7:
1.
5. The antibacterial and biodegradable packaging box coating based on chitosan-silver ions according to claim 1, characterized in that, The dry film thickness of the chitosan-silver ion confinement layer is 3–18 μm; the number of silver-containing aggregates with a maximum outer diameter greater than 250 nm in any 100 μm × 100 μm observation area is no more than 6.
6. The antibacterial and biodegradable packaging box coating based on chitosan-silver ions according to claim 1, characterized in that, The wax microemulsion component in the biodegradable sealing layer is made of at least one of carnauba wax, rice bran wax, or beeswax. The dispersed phase particle size D50 of the waxy microemulsion component is 0.2–3 μm; The degree of esterification of the low-ester pectin is 20%–45%; The dry film thickness of the biodegradable sealing layer is 1–7 μm; The weight ratio of the waxy microemulsion component to the low-ester pectin is 1:0.2 to 1:1.
5.
7. A method for preparing an antibacterial and biodegradable packaging box coating based on chitosan-silver ions as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Substrate surface finishing: The surface of the biodegradable packaging box substrate to be coated is dusted, free fibers are removed, and plasma or corona treatment is performed to obtain a pretreated substrate with a surface moisture content of 5% to 11%. S2, Anchoring layer formation: An aqueous anchoring solution containing tannic acid, calcium salt and sodium carboxymethyl cellulose is applied to the surface of the pretreated substrate to be coated, and dried at 35-70°C to form the substrate anchoring layer; S3, Silver ion pre-complexation: Dissolve water-soluble chitosan in an aqueous medium, adjust the pH to 4.2-6.2, add silver salt and stir for 20-120 min to obtain chitosan-silver ion complex solution; S4. Preparation of confined coating solution: Add sodium alginate, citric acid and glycerol to chitosan-silver ion complex solution and stir until the viscosity is 80-900 mPa·s to obtain confined coating solution. S5. Formation of confinement layer: The confinement coating liquid is applied to the surface of the substrate anchoring layer and dried in sections at 40-85°C to form a chitosan-silver ion confinement layer. S6. Formation of the sealing layer: An aqueous sealing liquid containing waxy microemulsion components, low-ester pectin, polyvinyl alcohol and citric acid is coated on the surface of the chitosan-silver ion confinement layer and dried at 35-75°C to form a biodegradable sealing layer, thereby obtaining a packaging box with the aforementioned antibacterial and biodegradable packaging box coating.
8. The preparation method according to claim 7, characterized in that, In step S3, the mass concentration of water-soluble chitosan in the aqueous medium is 0.8%–6%, and silver salt is added dropwise to the water-soluble chitosan solution in the form of a 0.01–0.3 mol / L silver salt aqueous solution over a period of 15–80 min. The stirring speed during the dropwise addition process is 300–1000 r / min, and the mixture is stirred in the dark for 20–120 min after the dropwise addition is completed. In step S4, sodium alginate is added in the form of a sodium alginate aqueous solution with a mass concentration of 0.5%–5%.
9. The preparation method according to claim 7, characterized in that, The segmented drying in step S5 includes a first drying stage and a second drying stage: the temperature of the first drying stage is 40-55℃ and the time is 3-15 min; the temperature of the second drying stage is 60-85℃ and the time is 5-30 min.
10. The preparation method according to claim 7, characterized in that, The preparation of the aqueous sealing liquid in step S6 includes: melting the wax component at 60-90°C, and then mixing and emulsifying it with a low-ester pectin aqueous solution, a polyvinyl alcohol aqueous solution, and citric acid. The dispersed phase particle size D50 of the wax microemulsion component in the emulsified aqueous sealing liquid is 0.2-3 μm. The drying temperature in step S6 is lower than the temperature of the second drying stage in step S5.
Citation Information
Patent Citations
Hydrocolloid cellulose acetate fiber dressing for wound treatment and preparation process of hydrocolloid cellulose acetate fiber dressing
CN120960491A
Polyvinyl chitosan and tannic acid composite active membrane as well as preparation method and application thereof
CN122011473A